2011
DOI: 10.1007/s11099-011-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Damaging mechanisms of chilling- and salt stress to Arachis hypogaea L. leaves

et al.

Abstract: To investigate damaging mechanisms of chilling and salt stress to peanut (Arachis hypogaea L.) leaves, LuHua 14 was used in the present work upon exposure to chilling temperature (4°C) accompanied by high irradiance (1,200 μmol m -2 s -1 ) (CH), salt stress accompanied by high irradiance (1,200 μmol m -2 s -1 ) (SH), and high-irradiance stress (1,200 μmol m -2 s -1 ) at room temperature (25°C) (NH), respectively. Additionally, plants under low irradiance (100 μmol m -2 s -1 ) at room temperature (25°C) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 30 publications
0
25
0
1
Order By: Relevance
“…The photosynthetic parameter F 0 is related to chlorophyll content [54]. According to previous reports [55][56][57], F 0 increases when the photochemical apparatus is destructed or, more specifically, when the amount of functional chlorophylls not connected to the reaction centers of PSII. The decrease of F 0 is an indication of a high-energy dissipation in the minor antenna [56].…”
Section: Proteins Involved In Photosynthesismentioning
confidence: 92%
“…The photosynthetic parameter F 0 is related to chlorophyll content [54]. According to previous reports [55][56][57], F 0 increases when the photochemical apparatus is destructed or, more specifically, when the amount of functional chlorophylls not connected to the reaction centers of PSII. The decrease of F 0 is an indication of a high-energy dissipation in the minor antenna [56].…”
Section: Proteins Involved In Photosynthesismentioning
confidence: 92%
“…Previous studies on night temperatures have focused either on the effects of HNT and LNT alone (Friend, 1981; Seddigh and Jolliff, 1984a,b,c; Koscielniak, 1993; Bertamini et al, 2005) or the mixed effects of night temperatures and CO 2 concentration (Mortensen and Moe, 1992; Volder et al, 2004; Cheng et al, 2008, 2009, 2010), light period (Gimenez and Rumi, 1988; Turner and Ewing, 1988; Lee et al, 1991; Verheul et al, 2007), intensity (Bunce, 1985; Mortensen, 1994; Rapacz, 1998; Flexas and Osmond, 1999; Davies et al, 2002) as well as other environmental factors (Schoppach and Sadok, 2013) and growth regulators (Shah et al, 2011; Mohammed et al, 2013; Zhang et al, 2014). These experiments had been conducted on pineapple (Neales et al, 1980), peanut (Bagnall et al, 1988; Wang, 2007; Lin et al, 2011) and shrub-grass ecosystems (Beier et al, 2004). Although the interest in the influence of night temperatures on many aspects of plants is growing, studies are scattered and there lacks a synthetic study on how and to what extent night temperature change impacts terrestrial plant growth and biomass accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that salinity stress predisposes photosystem II (PSII) to photoinhibitory damage (Lu et al 2002;Maricle et al 2007;Hichem et al 2009;Qin et al 2010Qin et al , 2011Sui et al 2010). However, very little attention has been paid to the responses of PSII to salinity stress and high-temperature stress in combination (Henley et al 2002).…”
Section: Introductionmentioning
confidence: 99%